2021
DOI: 10.7595/management.fon.2021.0017
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Perception of CSR Activities: What Does it Mean for Companies?

Abstract: Research Question: The paper develops a conceptual model for exploring the factors which impact the consumers' word of mouth (WOM) and willingness to pay (WTP) for products and services of socially responsible companies. Motivation: The paper is based on the research of Castaldo et al. (2009), Pivato et al. (2007), Rim and Kim (2016), and Jarvis et al. (2017) concerning the consumers’ perception of corporate social responsibility (CSR) and measurement of the effectiveness of CSR activities. Accordingly, our pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 22 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…While this study primarily analysed the relationship between CSR and WTP from the perspective of consumer behaviour, it might be interesting to study the effect of detrimental corporate social performance of companies on consumer behaviour. Our analysis of studies has also revealed several mediators such as customer satisfaction , brand trust (Nikoli c et al, 2021) and so forth that are in the pathway of an effect between the independent and dependent variables. Future research can examine closely aligned factors like brand purpose and brand virtue for their mediation in the relationship between CSR and WTP.…”
Section: Contextmentioning
confidence: 78%
See 3 more Smart Citations
“…While this study primarily analysed the relationship between CSR and WTP from the perspective of consumer behaviour, it might be interesting to study the effect of detrimental corporate social performance of companies on consumer behaviour. Our analysis of studies has also revealed several mediators such as customer satisfaction , brand trust (Nikoli c et al, 2021) and so forth that are in the pathway of an effect between the independent and dependent variables. Future research can examine closely aligned factors like brand purpose and brand virtue for their mediation in the relationship between CSR and WTP.…”
Section: Contextmentioning
confidence: 78%
“…The socially responsible activities of companies lead consumers to self‐evaluate and view themselves positively as they associate themselves with contributing toward the greater good by purchasing CSR‐related goods (Bhattacharya & Sen, 2003). This can lead to consumer's willing to pay more (Marquina Feldman & Vasquez‐Parraga, 2013; Nikolić et al, 2021; Wei et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is believed that the pandemic could have significant impact on e-commerce market. Also, other constructs could be integrated in the model such as CSR activities of the company [30]. Another interesting direction of the research could be towards conducting a similar survey in the region and do a comparative study so as to observe the similarities and differences in the consumer behavior.…”
Section: Discussionmentioning
confidence: 99%